Public Health - Social and Behavioral Health 2012
DOI: 10.5772/37886
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Food Choice and Dietary Intake in Modern Western Societies

Abstract: Human behavior accounts for the majority of morbidity and premature mortality throughout the world. This book explores several areas of human behavior including physical activity, nutrition and food, addictive substances, gun violence, sexual transmitted diseases and more. Several cutting edge methods are also examined including empowering nurses, community based participatory research and nature therapy. Less well known public health topics including human trafficking, tuberculosis control in prisons and publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
151
5
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(178 citation statements)
references
References 90 publications
(109 reference statements)
16
151
5
6
Order By: Relevance
“…This illustrates, that both men and women have a habit in choosing healthy foods are relatively the same. The results of this study are not in line with the opinion of Arganini et al (2012) which states that women generally show a tendency to make healthy food choices and are much more concerned about the importance of healthy food choices. Other results in this study indicate that the health dimension is the main reason for men and women when choosing healthy foods.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This illustrates, that both men and women have a habit in choosing healthy foods are relatively the same. The results of this study are not in line with the opinion of Arganini et al (2012) which states that women generally show a tendency to make healthy food choices and are much more concerned about the importance of healthy food choices. Other results in this study indicate that the health dimension is the main reason for men and women when choosing healthy foods.…”
Section: Discussioncontrasting
confidence: 52%
“…Various types of food that offered today make consumers should be more selective, because not all of foods have good benefits for the body. Modern consumers have anxieties and contradictions in food and health (Mennell et al 1992;Rozin et al 1999;Arganini 2012). Healthy food is one of the supporting health.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, gender differences in responsibilities for meal preparation and food shopping (16), food preferences and intakes (17), nutrition knowledge (18), interest in learning about health and nutrition (19), and eating behaviors (20)(21)(22)(23) have been highlighted in the literature. These differences may influence the quality of diet and the degree of adherence to healthy dietary recommendations (24).…”
Section: Introductionmentioning
confidence: 99%
“…We think that this gender difference deserves further study, as food choices are an area in which research has revealed consistent behavioural gender differences. Food choice is dependent on a wide spectrum of factors, which affect human behaviour in different ways, resulting in the choice of some specific products and in the rejection of others [28]. Studies conducted in modern Western societies report consistent associations between gender and specific foods, where meat (especially red and processed meat), alcohol and hearty portion sizes are associated with masculinity, while vegetables, fruit, fish and sour dairy products (e.g.…”
Section: @Erspublicationsmentioning
confidence: 99%